ENHANCING SCHOOL REPUTATION THROUGH EFFECTIVE STAKEHOLDER ENGAGEMENT: A Qualitative Analysis at an Integrated Islamic Junior High School in Mojokerto - Chusnul Chotimah; Maulina Pia Wulandari; Zulkarnain Nasution (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2024)
This research investigates the pivotal role of stakeholder engagement in shaping the reputation and sustainable growth of an Integrated Islamic Junior High School in Mojokerto. Both internal stakeholders, such as school leadership, teachers, and administrative staff, along with external stakeholders, including parents and the parents' committee, significantly contribute to advancing the school’s educational, moral, and community objectives. The study aims to identify the roles of these stakeholders and propose a sustainable model for school growth that integrates Islamic values with modern educational practices. Using a qualitative approach, the research incorporates interviews, document analysis, and observations to analyze the dynamics between stakeholders. The findings reveal that internal stakeholders are key to fostering academic and moral development, while external stakeholders play an essential role in advocacy, community involvement, and providing feedback. This collaborative effort strengthens the school’s reputation and supports its mission. The research concludes that stakeholder engagement is essential for maintaining the school’s growth and focus on academic excellence and Islamic values. It recommends formalizing a stakeholder engagement strategy, establishing a code of ethics based on Islamic principles, and continuously adapting the curriculum to balance religious instruction with academic rigor for long-term sustainability.